Infectious viruses from transfected SARS-CoV-2 genomic RNA - Väisänen, Elina; Jiang, Miao; Laine, Larissa; Waris, Matti; Julkunen, Ilkka; Österlund, Pamela (Frontiers in Bioengineering and Biotechnology, 2023)
SARS-CoV-2 emerged at the end of 2019, and like other novel pathogens causing severe symptoms, WHO recommended heightened biosafety measures for laboratories working with the virus. The positive-stranded genomic RNA of coronaviruses has been known to be infectious since the 1970s, and overall, all experiments with the possibility of SARS-CoV-2 propagation are carried out in higher containment level laboratories. However, as SARS-CoV-2 RNA has been routinely handled in BSL-2 laboratories, the question of the true nature of RNA infectiousness has risen along with discussion of appropriatebiosafety measures. Here, we studied the ability of native SARS-CoV-2 genomic RNA to produce infectious viruses when transfected into permissive cells and discussed the biosafety control measures related to these assays. In transfection assays large quantities of genomic vRNA of SARS-CoV-2 was required for a successful production of infectious viruses. However, the quantity of vRNA alone was not the only factor, and especially when the transfected RNA was derived from infected cells, even small amounts of genomic vRNA was enough for an infection. Virus replication was found to start rapidly after transfection, and infectious viruses were detected in the cell culture media at 24h post-transfection. In addition, silica membrane-based kits were shown to be as good as traditional TRI-reagent based methods in extracting high-quality, 30kb-long genomic vRNA. Taken together, our data indicates that all transfection experiments with samples containing genomic SARS-CoV-2 RNA should be categorized as a propagative work and the work should be conducted only in a higher containment BSL-3 laboratory.